The Effectiveness of Monetary Instruments on Inflation from a Sharia Economic Perspective: An Empirical Study of the Money Supply and the BI Rate in Indonesia for the 2015–2024 Period - Abdul Azis. R; Nini Andriani; Ayu Putri Utami; Rizkiani Iskandar; Siti Aminah H.K; Wisra M (Universitas Muhammadiyah Palu, 2026)
Inflation is a major challenge in maintaining macroeconomic stability, including from an Islamic economic perspective that emphasizes justice and welfare. This study analyzes the effectiveness of the money supply (M2) and the BI Rate on inflation in Indonesia (2015–2024) using a quantitative approach using multiple linear regression. Time series data is taken from Bank Indonesia and analyzed using t-tests, F-tests, and coefficients of determination. The results show that M2 has a significant negative effect on inflation, indicating that monetary expansion directed at the real sector can stabilize prices. Conversely, the BI Rate has a significant positive effect, indicating the ineffectiveness of conventional interest rates in controlling inflation and the potential to trigger cost-push inflation. These findings strengthen criticism of usury-based instruments and encourage the need to develop sharia-compliant monetary policies oriented towards the productive sector. The implication is that monetary authorities need to reformulate policy instruments that align with Islamic principles, such as profit-sharing instruments, to achieve equitable price stability. This study contributes to the Islamic economics literature by highlighting the dilemma of the dual banking system and the urgency of monetary policy transformation. The limitations of this research lie in the limited number of variables, so further research is recommended to include other factors such as exchange rates and inflation expectations.